Wavelet Spatio-Temporal Change Detection on Multitemporal SAR Images - Rodney V. Fonseca; Rogerio G. Negri; Aluisio Pinheiro; Abdourrahmane Mahamane Atto (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2023)
In this article, we introduce the wavelet energies correlation screening (WECS), an unsupervised method to detect spatio-temporal changes on multitemporal SAR images. The procedure is based on wavelet approximation for the multitemporal images, wavelet energy apportionment, and ultrahigh-dimensional correlation screening for the wavelet coefficients. We show WECS's performance on simulated multitemporal image data. We also evaluate the proposed method on a time series of 85 Sentinel-1 images of a forest region at the border of Brazil and French Guiana. Comparisons with well-known change detection methods found in the literature highlight the proposal's superiority in terms of change detection accuracy. Additionally, the introduced method has simple architecture and low computational cost.